A case report of fatal outcome of cerebral venous sinus thrombosis with cerebral hemorrhage during early pregnancy secondary to antithrombin III deficiency - Elias, Nurezwana; Murajrajamany, Kavitha; Noor Azmi, Mat Adenan (Aras Part Medical International Press, 2018)
Objectives: Cerebral venous sinus thrombosis (CVST) with cerebral hemorrhage is relatively rare but may result in a catastrophic outcome. Antithrombin III deficiency is an inherited disease that contributes to an increase in the occurrence of thromboembolic events during pregnancy. Case Presentation: A nulliparous, 34-year-old Chinese woman at 9 weeks of pregnancy with underlying antithrombin III deficiency was under treatment with low dose molecular weight heparin. She presented with a frontal headache and projectile vomiting. A plain computed tomography (CT) scan and magnetic resonance angiography and venography (MRAV) of the brain showed features suggestive of CVST involving superior sagittal sinus with venous infarct and right frontal and left parietal intraparenchymal hemorrhage. During admission, she developed episodes of fainting and loss of consciousness. A repeated brain CT scan showed worsening intraparenchymal hemorrhages with midline shift, subfalcine herniation and cerebral edema. An emergency bilateral craniectomy was performed to relieve the intracranial pressure. Despite the surgery and supportive measures, the patient succumbed to death. Conclusion: Due to the highly hypercoagulable state of pregnancy with concomitant antithrombin III deficiency, preconception counselling including optimization of anticoagulant dosage is crucial. In addition, the administration of antithrombin III concentrate should be considered during pregnancy for women with antithrombin deficiency.